Optimization of electro-mechanical smart structures - Bänsch, Eberhard; Kaltenbacher, Manfred; Leugering, Günter; Schury, Fabian; Wein, Fabian (Constrained Optimization and Optimal Control for Partial Differential Equations, 2012)
We present topology optimization of piezoelectric loudspeakers using the SIMP method and topology gradient based methods along with analytical and numerical results.
Keywords: Topology optimization; piezoelectricity; loudspeakers